Antiepileptic Drug Phenobarbital: A Chemsketch Study - Laxmi, Katanguru (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
Phenobarbital belongs to the class of medications called barbiturates. It is used to treat insomnia (difficulty sleeping) and as a sedative to relieve the symptoms of anxiety or tension. It is also used for the control of certain types of seizures. It works by slowing down the brain and nervous system. Phenobarbital is a barbiturate, nonselective central nervous system depressant which is primarily used as a sedative hypnotic and also as an anticonvulsant in subhypnotic doses.